Regulation of thymidine kinase protein levels during myogenic withdrawal from the cell cycle is independent of mRNA regulation. - Gross, M K (1988)
Replication-dependent changes in levels of enzymes involved in DNA precursor biosynthesis are accompanied frequently by changes in levels of cognate mRNA. We tested the common assumption that changes in mRNA levels are responsible for growth-dependent expression of these enzymes using a line of mouse muscle cells that irreversibly withdraws from the cell cycle as part of its terminal differentiation program. Thymidine kinase (TK) mRNA, activity, and protein levels were quantitated in cells transformed with multiple copies of the chicken TK gene. The decline in TK mRNA (both whole cell and cytoplasmic) during myogenesis was poor (2-fold average) and variable (1.2 to 8-fold). In contrast, TK activity always was regulated efficiently (20-fold), even in cells which regulated TK mRNA very poorly. Thus, regulation of TK activity was independent of TK mRNA regulation as myoblasts withdrew from the cell cycle. A TK/beta-galactosidase fusion protein was used to derive an antibody against chicken TK. Immunoblot and immunoprecipitation analyses demonstrated TK protein levels, like TK activity levels, declined to a greater extent than TK mRNA levels. Thus, TK activity likely was regulated by a mechanism involving either decreased translation of TK mRNA or increased degradation of TK protein in committed muscle cells.